Uso del texto de planificación de nivel educación básica en los CECIBS :Centro Educativo Experiencial de Educación intercultural bilingüe de Quito CEDEIB - Q, Centro Experimental Piloto de Educación Comunitario Intercultural Bilingüe Mushuk Pacari y Centro Educativo Comunicativo Intercultural Trilingüe Particular YACHAY WASI. - Cepeda Guacho, Juan (2002)
Framework. Introduction. Problem Statement. Problem formulation. Systematization of the problem. Delimitation of the investigation. Spatial and temporal boundaries. Limits on the research and academic order Delimitation of the participating subjects. Goals. Justification of the investigation. Hypothesis. System variables. Indicators. Indices. The focus of the text is traditional. The structure of the text does not meet the reality of the one-teacher schools. Metología. Theoretical framework. Educaicón bilingual. General understanding of the use of the text of basic education in three schools of the bilingual intercultural jurisdiction of the province of Pichincha. Conclusions and recommendations. Conclusions. Glossary. Bibliography. Annexes.